PENGARUH STERILISASI DAN DOSIS PUPUK KANDANG TERHADAP PERTUMBUHAN UMBI CALLA LILY (Zanthedeschia elliottiana) - Krisantini, ,; Yusuf, M.; Tjia, B. (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1996)
The objective of the experiment was to find out if sterilization of the media prior to planting, combined with application of various rates of chicken manure for fertilization, would increase production of calla lily tubers with are 3 - 5 cm diameter size. The experiments used two plots, one with sterilized and the other with non-sterilized media and chicken manure. Small tubers with ± 1 cm diameter and had fulfilled their dormancy requirement were planted. Chicken manure was applied at four different rates: 3, 5, 7, 9 kg/m2, and replicated four times. Data were taken on height, fresh and dry weight of plants, number of leaves. and percentages of various tuber size, following harvest. Tubers showed better results in terms of fresh and dry weight, and percentages of larger than 3 cm diameters tubers. Highest yields were obtained with 3 kg/m2 chicken manure.